News readers’ discussions in Finland on reduced working time - Niemitz, Johanna (My University, 2024)
This thesis explores the Finnish news readers attitudes towards reduced working time back in the summer of 2021. News from other countries and specifically from Iceland of experiments of reduced working time were reported in the Finnish press. These news articles were commented on social media by Finns. The comments formulate the data used in this paper. The comments are analyzed using Causal Layered Analysis, to reveal, what kind of underlying worldviews and myths shape what Finns think about working time. In result of the analysis three futures images are presented that give a glimpse to the year 2060 and what the working hours could look like. The findings of the analysis are reflected upon the scientific research, and expert opinions on working time that formulate the framework for this thesis.
Keywords: CLA, futures images, shortened working time.